Obsessive-compulsive symptom dimensions in a population-based, cross-sectional sample of school-aged children - Alvarenga, Pedro G.; Cesar, Raony C.; Leckman, James F.; Moriyama, Tais S.; Torres, Albina R. [UNESP]; Bloch, Michael H.; Coughlin, Catherine G. [UNESP]; Hoexter, Marcelo Q.; Manfro, Gisele G.; Polanczyk, Guilherme V.; Miguel, Euripedes C.; Rosario, Maria C. do (Elsevier B.V., 2015)
Background: Obsessive-compulsive disorder can be expressed as four potentially overlapping obsessive-compulsive symptom (OCS) dimensions (OCSD) ("symmetry/ordering", "contamination/cleaning", "aggressive/sexual/religious" and "collecting/hoarding"). In clinical samples, some dimensions are more familial and associated with increased psychiatric comorbidity and malfunctioning. However, data concerning OCS and OCSD are scarce in non-clinical samples, particularly among children. The present study aims to estimate: (1) the prevalence and sex/age distribution of OCS/OCSD in a community-based sample of schoolchildren; (2) the association between OCS and additional clinical factors; and (3) the degree of familial aggregation of OCS/OCSD. Methods: OCS and OCSD were evaluated in 9937 Brazilian school-children (6-12 years-old) and their biological relatives using the Family History Screen. Data analyses included gradient estimated equations and post-hoc tests. Results: We included data on 9937 index-children, 3305 siblings (13-18 years-old), and 16,218 parents. Biological mothers were the informants in 87.6% of the interviews. OCS were present in 14.7% of the index-children; 15.6% of their siblings; 34.6% of their mothers and 12.1% of their fathers. The prevalence of OCS and each of the OCSD gradually increased from ages 6 to 12 years. Overall, OCS in children were associated with the presence of other psychiatric symptoms, as well as behavioral/school impairment. OCS and each of the four OCSD aggregated significantly within families. Conclusions: OCS are prevalent and associated with psychiatric symptoms and clinical impairment among school-aged children. OCSD aggregate within families in a dimension-specific fashion. These findings suggest a natural continuum between OCS and OCD with regard to their dimensional character. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Epidemiology; Family history; Obsessive-compulsive disorder; School children